1983
DOI: 10.1002/jrs.1250140107
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic investigations of the CrO/Cr2O equilibrium in aqueous solution

Abstract: With the intention of doing a study of the CrO:-/Cr,O:-equilibrium in aqueous solution, we have carefully re-examined the Raman spectra of CrO:-, Cr,O:-and CICrO;. Diluting stepwise an aqueous solution of 00:-ion we have showed the non-existence of the HCrO; species which was previously considered to exist in such systems. By studying the effect of pH on the Raman spectra we calculated the constant for the equilibrium: 2 Cr0:-+ 2H'S Cr20:-+H20 to be log (jZ2 = 13.77 k 0.02 (20 "C and KNO, 0.8 M). Using this va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 25 publications
5
36
0
1
Order By: Relevance
“…The intense peak at ca 844 cm 1 , observed in the case of strongly alkaline solutions, becomes progressively less intense and ultimately vanishes upon acidification of the solution. This peak is clearly to be associated with CrO 4 2 vibrations, and the observed wavenumber of the maximum agrees closely with that reported in earlier studies. 4,5 At a shift of ca 899 cm 1 , a second intense band is seen in the spectra of solutions of low pH c ; its intensity progressively decreases with increasing pH c .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The intense peak at ca 844 cm 1 , observed in the case of strongly alkaline solutions, becomes progressively less intense and ultimately vanishes upon acidification of the solution. This peak is clearly to be associated with CrO 4 2 vibrations, and the observed wavenumber of the maximum agrees closely with that reported in earlier studies. 4,5 At a shift of ca 899 cm 1 , a second intense band is seen in the spectra of solutions of low pH c ; its intensity progressively decreases with increasing pH c .…”
Section: Resultssupporting
confidence: 92%
“…The accumulated evidence supporting the existence of HCrO 4 in the simultaneous equilibria CrO 4 2 C H C HCrO 4 1 2CrO 4 2 C 2H C Cr 2 O 7 2 C H 2 O 2 in aqueous media of pH ³ 3-10 now seems to be fairly conclusive. 1 It was the interpretation of Raman data by Michel and co-workers 4 (1) and (2) were considered, rather than only (2).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Ϫ , the existence of the aqueous species was denied in a "seemingly quite convincing way," (Cruywagen et al, 1998) by Poulopoulo et al (1997 (but see also Michel and Machiroux, 1983;Michel and Cahay, 1986). Their observations promoted new spectrophotometric (Cruywagen et al, 1998), Raman spectroscopic (Heyns et al, 1999), and infrared and X-ray (Hoffmann et al, 2001) investigations, which all confirmed the results of the potentiometric experiment of Palmer et al (1987), consistent with the data of Dellien et al (1976) (G°f ,298.15,aq HCrO 4 Ϫ ϭ Ϫ764.8 kJ/mol).…”
Section: Discussionmentioning
confidence: 94%
“…Por outro lado, ainda existe controvérsia na literatura sobre as espécies de Cr(VI) presentes em solução aquosa, os seus espectros e os valores das constantes de equilíbrio envolvidas. Por exemplo, nos anos 80, Michel et al [9][10] , analisando espectros Raman, indicavam que CrO 4 2-e Cr 2 O 7 2-eram as únicas espécies de Cr(VI) presentes em solução aquosa, negando a existência de espécies protonadas. Estudos recentes, como o de Poulopoulou et al 11 , analisando espectros no UV/visível, continuam questionando a presença da espécie HCrO 4 -em soluções aquosas.…”
unclassified